The Effect of Professional Ethics in Tax Decision-Making by Accountants in Multinational Companies - Novi Khoiriawati; Heru; Muhsin; Subur Harahap; Gilbert Rely (Institut Bisnis dan Informatika Kesatuan, 2025)
Professional ethics are a fundamental aspect of tax accounting practice, especially for multinational companies that face the complexity of cross-border regulations as well as pressure on business interests. This study aims to analyze the influence of professional ethics on tax decision-making by accountants, taking into account tax compliance intentions as a mediating variable and management pressure as a moderation variable. The study used a quantitative approach through a survey of 236 accountants working in multinational companies in Indonesia. Data were collected using a structured questionnaire and analyzed using the SEM-PLS method. The results of the study show that professional ethics have a significant positive effect on the quality of tax decisions, both directly and through the mediating role of tax compliance intentions. However, management pressure weakens the relationship, which suggests an ethical dilemma for accountants when dealing with the company's profit orientation. These findings underscore the importance of implementing ethics training, strengthening corporate governance, and internal control policies that drive tax compliance. Theoretically, the study expands the literature on the relationship between professional ethics and tax behavior in a multinational context, while practically providing recommendations for companies and regulators to balance business interests with compliance with tax law.